Social education politics in a Europe of inequalities - Javier Bascuñan Cortés (Springer, 2013)
The aim of this research is to analyse some indicators which allow us to understand the current state of social education politics in Europe, with special reference to Spain. Some European and Spanish social and educational policies which try to confront the challenges of the current financial crisis are also explained. Some deficiencies, failures and contradictions attached to the process of the construction of European citizenship are pointed out. Some key topics which seem to foresee a deeper social and democratic crisis apart from the economic one are tackled. It is explained how the new forms of inequality evidence the failure of some of the important declarations of intent and objectives of the European Union. The subjection of social and democratic aspects to neoliberal economy -i.e. the negation of ideologies- is questioned. To conclude, some key topics are proposed as the central axis through which it could be possible to redefine the content of social education politics in Europe and Spain and to set the bases of a new democratic European citizenship